Growth Hormone Receptor Gene Expression Increase Reflects Nutritional Status Improvement in Patients Affected by Crohn's Disease - Pagani, Sara; Bozzola, Elena; Strisciuglio, Caterina; Meazza, Cristina; Miele, Erasmo; Malamisura, M.; De Angelis, Paola; Bozzola, Mauro (Frontiers in Pediatrics, 2018)
Background We proposed to verify growth hormone receptor gene expression role in the growth failure of children with Crohn disease (CD). Methods. We measured serum growth hormone binding protein (GHBP) and insulin-like growth factor-I (IGF-I) levels, and growth hormone receptor (GHR) gene expression in pheripheral blood mononuclear cells of 21 patients with CD (before and after therapy) and in 27 age-sex-matched controls. Results. At diagnosis, significantly lower insulin-like growth factor-I and growth hormone binding protein levels were found in the CD group compared to the controls. Growth hormone receptor mRNA expression was lower in patients at diagnosis compared to the controls, even if the difference did not reach statistical significance, and significantly increased in patients one year later. Insulin-like growth factor-I levels significantly improved one year after diagnosis compared to basal levels. On the contrary, growth hormone binding protein values did not significantly change after one year of therapy. Conclusion. Our study raises the hypothesis of another mechanism through which cytokines interact with the growth hormone / insulin-like growth factor-I (GH/IGF-I) axis.